Supply Chain Information System for Revenue Collection of the Revenue Department in Thailand - Artaphon Chansamut (ExcelingTech, 2023)
The article about supply chain Information system for revenue collection of the Revenue Department in Thailand aim to present tax management through a supply chain applying for better effective tax management The tax management needs to be appropriate to changes of globalized economy and society. The processes consisted of Suppliers, The revenue department , Finished tax, Customers ,All component connect with information communication technology in the Thailand with the supply chain. This truly added the revenue department in Thailand .The supply chain and information system may be applied in the tax to support the tasks.